Implement a Computer Mouse Control for Quadriplegic Disability Using Camera - Ngo, Nguyen Hoai; Nguyen, Uyen Dinh; Lam, Nguyen Ngoc; Long, Chu Ba (AETA 2016: Recent Advances in Electrical Engineering and Related Sciences, 2017)
In the development of the digital-era, the applications of image processing are expanded in all sectors, such areas as health, military, technology, and daily life. In this paper, we will focus on developing a mouse control, specifically, for spinal cord injury person. For a person with quadriplegic disability, it is difficult for him/her to use the computer mouse or touchpad. Therefore, this paper proposes using the eye movement to control the computer mouse. Only one camera will be placed in front of the user’s face. The program will provide a tool to help the quadriplegic disabled operating the computer mouse by analyzing the motion of the iris and the appearance of sclera using the morphological operators. The program is written in MATLAB programming language with the support of Image Processing Toolbox.